Soil carbon concentration drives anoxic microsites across horizons, textures, and aggregate position in a California grassland - Emily M. Lacroix; Anna Gomes; Alexander S. Honeyman; Katie R. Huy; Scott Fendorf; Vincent Noël; Meret Aeppli (Geoderma)
Anoxic microsites, zones of oxygen depletion in otherwise well-aerated soils, serve as prominent controls on several biogeochemical cycles (e.g., carbon, nitrogen, iron). However, relatively little is known about the spatiotemporal distribution of anoxic microsites and thus little is known about their biogeochemical influence. Here, we use time-integrative measures of past anoxia (i.e., electrochemical measurements and quantification of anaerobic functional genes) to determine how the spatial distribution of anoxic microsites varies between aggregate interiors and bulk soils in soils of two distinct textures across multiple depths in a California grassland. We found greater evidence of anoxia in topsoils vs. subsoils and finer vs. coarse-textured soils. Counter to many traditional depictions of soil aggregates, we observed that aggregate interiors showed equal or less evidence of anoxic microsites than bulk soils. Across the entire dataset, our combined proxies for anoxic microsite prevalence were strongly and positively correlated with organic C concentration (R2 = 0.80), highlighting the importance of soil organic C availability and microbial oxygen demand in creating anoxic microsites. Our results contribute to a growing body of evidence that soil oxygen demand (i.e., microbial respiration) can play a more prominent role in anoxic microsite formation than soil oxygen supply, provoking questions about the suitability of using aggregate size and moisture as lone proxies for soil oxygen availability.